Hydrologic impact assessment of climate change on small catchment areas in Calabarzon, Philippines - Rivera, Ronald Michael M.
The Philippines is threatened by the possible impacts of climate change, and vast and considerable effects is expected to hit the country. The future hydrological impacts of climate change, particularly peak flow rate and precipitation, on a small pilot catchment area were simulated. Global Climate Models (GCMs) was used to simulate changes on precipitation based from the Intergovernmental Panel on Climate Change (IPCC) scenarios A2 and A1b. Emission scenario A2 describes a society in which the underlying theme is self-reliance, and emission scenario A1b indicates a future world with very rapid economic and technological growth. The coarse spatial resolution of the GCMs prevented the direct application of GCM simulations to hydrologic models and small catchment areas. The resolution was downscaled to a scale that can be applied to the pilot area. Two downscaling techniques was employed in the study. These two were Regional Climate Model (RCM), and simple constant scaling method. The results from the simulations of precipitation from the RCM were entered to HEC-HMS (Hydrologic Engineering Center - Hydrologic Modeling System), which projected the changes on peak flow of the study area due to climate change. The maximum increase in precipitation was simulated to be 26.7% to occur during the southwest monsoon season under scenario A2. On the other hand, the maximum increase in peak flow was simulated to be 31.29% under scenario A2 of the year 2020.